Microbial composite material for improving concrete crack repairing effect and preparation method and application thereof

By using microbial composite materials and optimized restoration processes, the problems of limited width and uneven cementing of microbial repair concrete cracks are solved, the crack repair effect and material compatibility are improved, and more efficient concrete crack repair is achieved.

CN119118576APending Publication Date: 2024-12-13ZHEJIANG SCI RES INST OF TRANSPORT +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411116297.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing microbial concrete crack repair technology ensures the repair width, and the cementation of the repair solution and auxiliary materials is uneven, affecting the repair effect.

Method used

Microbial composite materials are used, including repair solution A and repair solution B. Repair solution A is the fermentation liquid of Basilica Pasteurium, Repair solution B is a mixed aqueous solution of urea and calcium acetate, and the auxiliary materials are volcanic stone, ceratops and aluminum oxide. , through the repair process of low-temperature injection of repair liquid and step-by-step filling of auxiliary materials, the components and concentration of repair liquid, as well as the types and particle size of auxiliary materials.

Benefits of technology

It improves the repair effect of concrete cracks, enhances the uniformity and repair effect of material cementation, improves compressive strength and permeability, and has strong process operability and is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118576A_ABST
    Figure CN119118576A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of crossing of microorganisms and civil engineering, and discloses a microbial composite material for improving the repairing effect of concrete cracks, the composite material comprises a repairing liquid A, a repairing liquid B and an auxiliary material; the volume ratio of the repairing liquid A to the repairing liquid B is 1: 1; the repair liquid A is one of a sporosarcina pasteurii fermentation liquid, a fermentation supernatant, a thallus solution, a urease crude extract containing broken thalli and a urease crude extract; the repairing liquid B is a mixed aqueous solution of urea and calcium acetate, the ratio of the amount of substance of the urea to the amount of substance of the calcium acetate is 1: 1, the solvent is water, and the concentration of the calcium acetate is 0.5-2 mol / L; the auxiliary materials comprise vesuvianite, ceramsite and aluminum oxide. According to the method, the concentration of the microbial solution and the repairing liquid required for repairing the cracks and the types and particle sizes of auxiliary materials are optimized, so that the cracks are better repaired, and the crack repairing effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the cross-technical field of microorganisms and civil engineering, and in particular to a microbial composite material for improving the repair effect of concrete cracks, a preparation method and an application thereof. Background Art

[0002] Concrete is the most commonly used building material in the field of civil engineering. It has excellent mechanical strength and durability as well as low production cost advantages. However, during the service life of concrete, the concrete structure will degrade due to the influence of chemical and physical environment, and micro cracks will be generated inside and on the surface of the concrete structure. After the concrete structure cracks, it is necessary to repair it in time and continuously innovate crack repair technology to improve the service life of the concrete structure. The current non-biological concrete repair method has achieved certain results in engineering practice, but there are still many shortcomings. Microbial induced calcium carbonate precipitation technology has shown its unique advantages. The mechanism of this technology is simple, the operation is fast and efficient, and it is not only low in cost, but also environmentally friendly. However, the width of cracks repaired by microorganisms is limited. In existing reports, for concrete cracks repaired only by bacteria, the width of the repaired cracks is almost no more than 1mm while ensuring the repair effect. Therefore, it is often necessary to add some auxiliary materials to repair wide cracks. When repairing, appropriate auxiliary materials are selected to fill the cracks. Subsequently, a mixed solution of bacterial solution, urea and calcium source is added multiple times. Under suitable external conditions, some substances with cementing properties secreted by microorganisms make the fillers inside the cracks cemented into a whole, and finally the cracks are repaired. Whether the overall bonding between material particles is uniform and tight is the key to affecting the repair effect. When the bacterial solution is mixed with urea and calcium source solution, Ca 2+ CO3 produced by mineralization reaction 2- Rapid combination and aggregation result in the formation of a large amount of calcium carbonate precipitation in a short period of time, which blocks the pores formed by the material particles, making it difficult for the subsequent repair fluid to penetrate, resulting in uneven biocementation and affecting the repair effect.

[0003] Chinese patent application number CN116480179A discloses a biological repair method for deep micro-cracks in concrete structure and proposes different repair processes according to the width of the cracks in its application: injection repair is selected for cracks with a width of 0.3 to 1 mm; injection repair is selected after layered filling materials are selected for cracks with a width of 1 to 3 mm. The repair fluid and filling materials used in the repair are not studied in depth, and the repair effect is limited. In the present invention, the composition and concentration of the repair fluid and the type and particle size of the auxiliary materials are optimized respectively. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies in the prior art and to provide a microbial composite material for improving the repair effect of concrete cracks, as well as a preparation method and application thereof.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] A microbial composite material for improving the repair effect of concrete cracks, the composite material comprising a repair liquid A, a repair liquid B and auxiliary materials;

[0007] Wherein, the volume ratio of the repair liquid A to the repair liquid B is 1:1;

[0008] The repair solution A is one of the following: a fermentation solution of Sporosarcina pasteurianum, a fermentation supernatant, a bacterial solution, a crude urease extract containing broken bacterial cells, and a crude urease extract;

[0009] The repair solution B is a mixed aqueous solution of urea and calcium acetate, the molar ratio of the two is 1:1, the solvent is water, and the concentration of calcium acetate is 0.5-2 mol / L;

[0010] The auxiliary materials include volcanic rock, ceramsite and alumina.

[0011] Furthermore, the repair liquid A is a fermentation liquid of Bacillus pasteurianus; the concentration of calcium acetate in the repair liquid B is 1.5 mol / L; and the particle sizes of the auxiliary materials include 0.1-0.2 mm, 0.2-0.4 mm, 0.4-0.6 mm, 0.6-0.8 mm and 0.8-1.5 mm.

[0012] Furthermore, the auxiliary material is ceramsite, and the particle size of the ceramsite is 0.4-0.6 mm.

[0013] Furthermore, the culture medium components and contents used for preparing the fermentation broth of Bacillus pasteurianus are: 25-30 g / L yeast extract, 8-12 g / L ammonium sulfate, 5-8 g / L peptone, 0.1-0.2 mol / L urea, 0.13 mol / L Tris, the solvent is water, and the pH value is adjusted to 8.5-9.5 with 2 mol / L HCl; the activation culture conditions of Bacillus pasteurianus are 28-35° C., 180-220 r / min, and shaking culture for 15-18 h; after activation, the expansion culture is carried out under the conditions of 28-35° C., 180-220 r / min, and shaking culture for 24-30 h.

[0014] Application of the microbial composite material as described above in concrete crack repair.

[0015] The method for improving the repair effect of concrete cracks by using the microbial composite material as described above adopts a repair process of injecting repair liquid A and repair liquid B at low temperature and filling auxiliary materials in steps to repair cracks, so as to improve the crack repair effect.

[0016] Furthermore, the method comprises the following steps: filling auxiliary materials step by step, i.e. filling the crack with auxiliary materials ≤1.5cm high, ensuring that the materials are evenly accumulated in the crack, directly mixing the repair liquid A stored in a 4°C refrigerator with the repair liquid B at a volume ratio of 1:1, and using a medical syringe to absorb the mixed solution and slowly inject it into the crack along the crack mouth. This is a repair test, and the repair is carried out twice a day with a time interval of 6h between each repair. After the materials are cemented, fill them with auxiliary materials ≤1.5cm high, and repeat the above steps until the crack is completely repaired.

[0017] Furthermore, the initial temperature when the repair fluid is injected is ≤5°C.

[0018] The advantages and positive effects achieved by the present invention are:

[0019] 1. The microbial composite material in the present invention includes a repair liquid and auxiliary materials. The composition and concentration of the repair liquid and the types and particle sizes of the auxiliary materials are optimized and combined into a microbial composite material. The repair process of injecting the repair liquid at low temperature and filling the auxiliary materials in steps is used to repair cracks to improve the crack repair effect. Compared with the existing non-biological repair methods, the repair process is highly operable, and the microbial composite material has good compatibility with concrete materials. In the present invention, the microbial solution, repair liquid concentration, and auxiliary material types and particle sizes required for repairing cracks are optimized, which is more conducive to repairing cracks and improving the crack repair effect.

[0020] 2. In the method of the present invention, low-temperature injection of repair fluid and step-by-step addition of auxiliary materials can make the material bonding more uniform, thereby improving the crack repair effect.

[0021] 3. The method of the present invention utilizes microbial remediation, which is greener and more environmentally friendly than existing non-biological methods and has good compatibility with concrete materials.

[0022] 4. The present invention optimizes the composition and concentration of the repair liquid and the type and particle size of the auxiliary materials to form a microbial composite material, and adopts a repair process of injecting the repair liquid at low temperature and filling the auxiliary materials step by step to repair the cracks to improve the crack repair effect. Through the crack repair test, the apparent repair effect, compressive strength and impermeability are used as evaluation indicators to optimize the material type and particle size. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The electron microscope images of the mineralized products of different repair solutions A in the present invention;

[0024] Figure 2 It is a graph of mineralization yield of repair solution B with different concentrations in the present invention;

[0025] Figure 3 This is a diagram of the surface state of the test piece after being repaired with different auxiliary materials in the present invention;

[0026] Figure 4 The test results of the specimens repaired with different auxiliary materials in the present invention are shown in FIG. 1 , wherein (a) is a compressive strength test, and (b) is a water absorption test;

[0027] Figure 5 This is a diagram of the surface state of the test piece after being repaired by ceramsite with different particle sizes in the present invention;

[0028] Figure 6 The figures are test results of the specimens assisted by ceramsite with different particle sizes in the present invention; wherein (a) is a compressive strength test, and (b) is a water absorption test;

[0029] Figure 7 is a graph of urease activity at different temperatures in the present invention;

[0030] Figure 8 The surface state diagram of the repaired specimens of Example 4 and the comparative example in the present invention;

[0031] Fig. 9 The figures are test results of the repaired specimens of Example 4 and the comparative example of the present invention; wherein (a) is a compressive strength test, and (b) is a water absorption test. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with the embodiments. The following embodiments are descriptive rather than restrictive, and the protection scope of the present invention cannot be limited by the following embodiments.

[0033] The various experimental operations involved in the specific embodiments are all routine techniques in the art. For parts not specially annotated in this document, ordinary technicians in the art can implement them by referring to various commonly used reference books, scientific and technological literature or related instructions, manuals, etc. before the filing date of this invention.

[0034] A microbial composite material for improving the repair effect of concrete cracks, the composite material comprising a repair liquid A, a repair liquid B and auxiliary materials;

[0035] Wherein, the volume ratio of the repair liquid A to the repair liquid B is 1:1;

[0036] The repair solution A is one of the following: a fermentation solution of Sporosarcina pasteurianum, a fermentation supernatant, a bacterial solution, a crude urease extract containing broken bacterial cells, and a crude urease extract;

[0037] The repair solution B is a mixed aqueous solution of urea and calcium acetate, the molar ratio of the two is 1:1, the solvent is water, and the concentration of calcium acetate is 0.5-2 mol / L;

[0038] The auxiliary materials include volcanic rock, ceramsite and alumina.

[0039] Preferably, the repair solution A is a fermentation solution of Bacillus pasteurianus; the concentration of calcium acetate in the repair solution B is 1.5 mol / L; and the particle sizes of the auxiliary materials include 0.1-0.2 mm, 0.2-0.4 mm, 0.4-0.6 mm, 0.6-0.8 mm and 0.8-1.5 mm.

[0040] Preferably, the auxiliary material is ceramsite, and the particle size of the ceramsite is 0.4-0.6 mm.

[0041] Preferably, the culture medium components and contents used for preparing the fermentation broth of Bacillus pasteurianus are: 25-30 g / L yeast extract, 8-12 g / L ammonium sulfate, 5-8 g / L peptone, 0.1-0.2 mol / L urea, 0.13 mol / L Tris, the solvent is water, and the pH value is adjusted to 8.5-9.5 with 2 mol / L HCl; the activation culture conditions of Bacillus pasteurianus are 28-35°C, 180-220 r / min, and shaking culture for 15-18 h; after activation, the expansion culture is carried out under the conditions of 28-35°C, 180-220 r / min, and shaking culture for 24-30 h.

[0042] Application of the microbial composite material as described above in concrete crack repair.

[0043] The method for improving the repair effect of concrete cracks by using the microbial composite material as described above adopts a repair process of injecting repair liquid A and repair liquid B at low temperature and filling auxiliary materials in steps to repair cracks, so as to improve the crack repair effect.

[0044] Preferably, the method comprises the following steps: filling auxiliary materials step by step, i.e. filling the crack with auxiliary materials ≤1.5cm high, ensuring that the materials are evenly accumulated in the crack, directly mixing the repair liquid A stored in a 4°C refrigerator with the repair liquid B at a volume ratio of 1:1, using a medical syringe to absorb the mixed solution and slowly inject it into the crack along the crack mouth, which is a repair test, and repairing is carried out twice a day with an interval of 6h between each repair, and after the materials are cemented, filling with auxiliary materials ≤1.5cm high, repeating the above steps until the crack is completely repaired.

[0045] Preferably, the initial temperature when the repair fluid is injected is ≤5°C.

[0046] Specifically, the relevant preparation and detection are as follows:

[0047] Repair solution A is a pasteurian spore octahedralis bacterial solution fermented to the stable period. The culture medium components and contents used in the preparation of the bacterial fermentation solution are: yeast extract 25-30g / L, ammonium sulfate 8-12g / L, peptone 5-8g / L, urea 0.1-0.2mol / L, 0.13mol / LTris, the solvent is water, and the pH value is adjusted to 8.5-9.5 with 2mol / L HCl. The activation culture conditions of pasteurian spore octahedralis are 28-35℃, 180-220r / min, and shaking culture for 15-18h. After activation, the culture is expanded under the conditions of 28-35℃, 180-220r / min, and shaking culture for 24-30h.

[0048] Repair solution B is a mixed solution of urea and calcium acetate, with a molar ratio of 1:1, a concentration of 1.5 mol / L, and the solvent is water.

[0049] The specific steps of the mineralization reaction are as follows: select 0.4-0.6mm expanded clay as the auxiliary material, fill the auxiliary material in steps, that is, fill the crack with auxiliary materials ≤1.5cm high to ensure that the material is evenly accumulated in the crack, and directly mix the repair solution A stored in a 4℃ refrigerator with 1.5mol / L repair solution B in a volume ratio of 1:1. Use a medical syringe to absorb the mixed solution and slowly inject it into the crack along the crack mouth. This is a repair test. Repairs are carried out twice a day with an interval of 6h between each repair. After the materials are cemented, fill them with auxiliary materials ≤1.5cm high and repeat the above steps until the crack is completely repaired.

[0050] The relevant optimization process is as follows:

[0051] The composition and concentration of the repair fluid as well as the type and particle size of the auxiliary materials are optimized and combined into a microbial composite material. The cracks are repaired using a repair process that injects the repair fluid at low temperature and fills the auxiliary materials in steps to improve the crack repair effect.

[0052] Example 1

[0053] The optimized components of repair solution A are: fermentation broth of Sporosarcina pasteurianus, fermentation supernatant, bacterial solution, crude urease extract containing broken bacterial bodies, and crude urease extract, preferably fermentation broth of Sporosarcina pasteurianus.

[0054] The preparation method of the pasteurian spore octahedral bacterial liquid is as follows: using a culture medium for activation culture, the activation culture conditions are 28-35°C, 180-220r / min, and shaking culture for 15-18h; after activation, expansion culture is performed under the conditions of 28-35°C, 180-220r / min, and shaking culture for 22-24h to obtain pasteurian spore octahedral bacterial liquid, and after activation, expansion culture is performed under the conditions of 28-35°C, 180-220r / min, and shaking culture for 24-30h to obtain pasteurian spore octahedral bacterial liquid fermented to a stable period, that is, pasteurian spore octahedral fermentation liquid. Take four equal portions of pasteurian spore octahedral bacterial liquid fermented to a stable period for preparing a solution. The untreated bacterial solution was numbered A, and three portions of the bacterial solution were centrifuged at 4000rpm for 5min to obtain bacterial precipitates and supernatant. The supernatant was retained and numbered B. The bacterial precipitates were resuspended with PBS solution (0.02mol / L, pH 8.0) to obtain three bacterial solutions, numbered C; two portions of the bacterial solutions were ultrasonically disrupted at 45% power, 3s for 3s, and 30min for disruption to obtain a crude urease extract containing disrupted bacteria, numbered D; one portion of the crude urease extract containing disrupted bacteria was centrifuged at 4000rpm for 10min to obtain a crude urease extract, numbered E.

[0055] The mineralization reaction was carried out with a mixed solution of urea and calcium acetate (the molar ratio of urea to calcium salt was 1:1, and the concentration was 1.5-2 mol / L). The reaction was terminated after 24 hours, and the mineralization reaction product was preserved (the purpose of this step of the experiment was to select the repair solution A through electron microscopy observation of the product, and then use it for crack repair). The results of electron microscopy observation of the sample were as follows Figure 1 As shown. Through electron microscopy, calcium carbonate crystals in the mineralization reaction of urease crude extract are mostly dispersed spheres and are not stacked, but relatively loose. The product crystals of the mineralization reaction with the participation of bacteria are in a stacked state, and calcium carbonate with cementing effect is needed to repair cracks. When preparing urease crude extract, the bacteria need to be crushed, and the preparation process is more complicated. Finally, bacterial fermentation liquid was selected as repair liquid A.

[0056] The components and contents of the culture medium used for preparing the bacterial fermentation broth are: 25-30 g / L yeast extract, 8-12 g / L ammonium sulfate, 5-8 g / L peptone, 0.1-0.2 mol / L urea, 0.13 mol / LTris, the solvent is water, and the pH value is adjusted to 8.5-9.5 with 2 mol / L HCl. The activation culture conditions of Bacillus pasteurianus are 28-35°C, 180-220 r / min, and shaking culture for 15-18 hours. After activation, the culture is expanded under the conditions of 28-35°C, 180-220 r / min, and shaking culture for 24-30 hours.

[0057] Example 2

[0058] Optimize the concentration of repair solution B:

[0059] Repair solution B is a mixed solution of urea and calcium acetate, the molar ratio of the two is 1:1, the solvent is water, and different concentrations of repair solution B, i.e. 0.5, 1, 1.5, 2 mol / L, are mixed with repair solution A, i.e., fermentation broth of Bacillus pasteurianus, in a volume ratio of 1:1, and placed in a constant temperature incubator at 30°C for mineralization for 24 hours. Figure 2 As shown in the figure, when the concentration of repair solution B is 0.5, 1, and 1.5 mol / L, Ca 2+ When the utilization rate is 100% and the Ca content is 2 mol / L, 2+ The utilization rate is 85.36%, which is not completely utilized. Considering that 2 mol / L calcium acetate is difficult to dissolve at room temperature and the cost issue, the concentration of repair solution B is 1.5 mol / L.

[0060] Example 3

[0061] Through crack repair tests, compressive strength and impermeability are used as evaluation indicators to optimize material types and particle sizes. After cracks occur in concrete structures due to various reasons, the obvious weakening of its mechanical properties is one of the main characteristics of its damage. The compressive strength of the specimen is one of the commonly measured indicators. The higher the compressive strength, the better the crack repair effect. The electro-hydraulic servo pressure testing machine is used for testing.

[0062] Compressive strength recovery rate (%) = C1 / C0×100%

[0063] Where: C1 represents the strength of the specimen after crack repair, MPa;

[0064] C0 represents the strength of the complete specimen, MPa.

[0065] Due to the formation of cracks, the surface area exposed to water increases. When the crack surface contacts water, the crack absorbs water and increases the mass of the specimen. Therefore, the smaller the water absorption rate, the better the effect of crack repair. First, place the specimen in an oven at 60°C for drying (until its mass loss rate within 24 hours is less than 0.1%), take it out and seal its four sides with paraffin wax (to ensure that the specimen absorbs water in one dimension during the water absorption process), and weigh M0; put a bracket in a flat-bottomed container, place the unwax-sealed test surface of the specimen on the bracket facing down, and slowly inject water into the container until the liquid level is about 10mm higher than the test surface of the specimen; when the water absorption is saturated, quickly wipe off the moisture on the surface of the specimen, and weigh M1

[0066] Water absorption (%) = (M1-M0) / M0×100%

[0067] Anti-seepage recovery rate (%) = E1 / E0×100%

[0068] Where: E0 represents the water absorption rate of the specimen after crack repair, %;

[0069] E1 represents the water absorption of the complete specimen, %.

[0070] Different auxiliary materials (ceramsite, volcanic stone and alumina) were filled into cracks with a depth of 2 cm respectively. The repair solution A stored in a 4°C refrigerator was placed in a water bath and bathed at 30°C for 1 hour to restore the normal vitality of the bacteria. Then it was directly mixed with 1.5 mol / L repair solution B in a volume ratio of 1:1. A medical syringe was used to draw the mixed solution and slowly injected into the crack along the crack mouth. This was a repair test. The repairs were carried out twice a day with an interval of 6 hours between each repair until the cracks were completely filled and repaired. The crack repair effects were compared to determine the most suitable auxiliary materials. Figure 3 The following are the surface conditions of the specimens repaired with different auxiliary materials. The test results are shown in Figure 4 As shown, the compressive strengths of the specimens repaired with filling materials into the cracks are similar, which are 42.1, 43.2, and 42.2 MPa, respectively. The water absorption rate of the specimens repaired with expanded clay is lower than that of the specimens repaired with the other two materials, indicating that the specimens repaired with expanded clay have good impermeability. Figure 4 The complete specimen in the figure refers to a complete specimen without cracks, which can be used for comparison.

[0071] Fill 2 cm deep cracks with ceramsite of different particle sizes (0.1-0.2 mm, 0.2-0.4 mm, 0.4-0.6 mm, 0.6-0.8 mm and 0.8-1.5 mm) respectively, place the repair solution A stored in a 4 ° C refrigerator in a water bath and bathe at 30 ° C for 1 hour to restore the normal vitality of the bacteria, and then directly mix it with 1.5 mol / L repair solution B at a volume ratio of 1:1. Use a medical syringe to draw the mixed solution and slowly inject it into the crack along the crack mouth. This is a repair test. Repair twice a day, with an interval of 6 hours between each repair, until the crack is completely filled and repaired. Compare the crack repair effect and determine the most suitable ceramsite particle size. Figure 5 The following are the surface conditions of the specimens after being repaired with ceramsite of different particle sizes. The test results are shown in Figure 6 As shown, the compressive strength of the specimens repaired with expanded clay filled with a particle size of 0.4-0.6 mm is the highest, the compressive strength recovery rate is 96.4%, and the water absorption rate of the specimens is the lowest, indicating that the repair effect is good.

[0072] To investigate the effect of temperature on urease activity (repair solution B was not involved, only the conductivity of repair solution A, i.e., bacterial solution, at different temperatures was tested using a conductivity meter), the urease activity was measured using the conductivity method at 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, and 40°C. The results are as follows Figure 7As shown in the figure, when the temperature of the bacterial solution is 5°C, the urease activity is 0. It is believed that the effect of delaying the mineralization reaction is best at this temperature. When the cracks are subsequently repaired, the initial temperature of the injected bacterial solution is controlled below 5°C.

[0073] Fill the auxiliary materials in steps, that is, fill the cracks with auxiliary materials ≤1.5cm high to ensure that the materials are evenly deposited in the cracks. Inject the repair liquid at low temperature to cement the materials and then fill them with auxiliary materials ≤1.5cm high. Repeat the above steps until the cracks are completely repaired.

[0074] Example 4

[0075] Repair solution A is a bacterial solution of Bacillus pasteurii that has been fermented to the stable period. The culture medium components and contents used in the preparation of the bacterial fermentation solution are: yeast extract 25-30g / L, ammonium sulfate 8-12g / L, peptone 5-8g / L, urea 0.1-0.2mol / L, 0.13mol / LTris, the solvent is water, and the pH value is adjusted to 8.5-9.5 with 2mol / L HCl. The activation culture conditions of Bacillus pasteurii are 28-35℃, 180-220r / min, and shaking culture for 15-18h. After activation, the culture is expanded under the conditions of 28-35℃, 180-220r / min, and shaking culture for 24-30h. Repair solution B is a mixed solution of urea and calcium acetate, the molar ratio is 1:1, the solvent is water, and the concentration is 1.5mol / L.

[0076] Select 0.4-0.6mm expanded clay as the auxiliary material, fill the auxiliary material in steps, that is, fill the crack with auxiliary material ≤1.5cm high to ensure that the material is evenly accumulated in the crack, and directly mix the repair liquid A stored in a 4℃ refrigerator with 1.5mol / L repair liquid B in a volume ratio of 1:1. Use a medical syringe to absorb the mixed solution and slowly inject it into the crack along the crack mouth. This is a repair test. Repairs are carried out twice a day with an interval of 6h between each repair. After the materials are cemented, fill them with auxiliary materials ≤1.5cm high and repeat the above steps until the crack is completely repaired.

[0077] Comparative Example:

[0078] Repair solution A is a bacterial solution of Bacillus pasteurii that has been fermented to the stable period. The culture medium components and contents used in the preparation of the bacterial fermentation solution are: yeast extract 25-30g / L, ammonium sulfate 8-12g / L, peptone 5-8g / L, urea 0.1-0.2mol / L, 0.13mol / LTris, the solvent is water, and the pH value is adjusted to 8.5-9.5 with 2mol / L HCl. The activation culture conditions of Bacillus pasteurii are 28-35℃, 180-220r / min, and shaking culture for 15-18h. After activation, the culture is expanded under the conditions of 28-35℃, 180-220r / min, and shaking culture for 24-30h. Repair solution B is a mixed solution of urea and calcium acetate, the molar ratio is 1:1, the solvent is water, and the concentration is 1.5mol / L.

[0079] Select 0.4-0.6mm expanded clay as the auxiliary material, and fill the material into the crack to ensure that the auxiliary material fills the crack and that the material is evenly accumulated in the crack during the filling process. Place the repair solution A stored in a 4°C refrigerator in a water bath and bathe it in 30°C water for 1 hour to restore the normal vitality of the bacteria, then mix it evenly with 1.5mol / L repair solution B in a volume ratio of 1:1. Use a medical syringe to draw up the mixed solution and slowly inject it into the crack along the crack mouth. This is a repair test, and the repair is carried out twice a day with an interval of 6 hours between each repair until the crack is completely filled and repaired.

[0080] Figure 8 The following are the surface status diagrams of the repaired specimens of Example 4 and the comparative example. The test results are shown in Fig. 9 As shown: the compressive strength of the specimen in Example 4 is higher than that of the comparative example and higher than that of the intact specimen, and the compressive strength recovery rate is 103.9%, while the compressive strength recovery rate of the specimen in the comparative example is 88.8%; the water absorption rate of the specimen in Example 4 is close to that of the intact specimen, and the impermeability recovery rate is 86.9%, while the water absorption rate of the specimen in the comparative example is between the water absorption rates of the intact specimen and the unrepaired specimen, and the impermeability recovery rate is 71.2%. This shows that the repair process of injecting the repair fluid at low temperature and filling the auxiliary materials step by step in Example 4 can make the auxiliary materials fully bonded, thereby improving the crack repair effect.

[0081] At the same time, it can be seen from Example 4 and the comparative example that the repair liquid A, the repair liquid B and "the repair liquid A stored in a 4°C refrigerator is directly mixed with the repair liquid B in a volume ratio of 1:1" in the present invention have a synergistic effect, which can synergistically improve the repair effect of the repaired cracks, especially the repair liquid A in a 4°C refrigerator and the 1.5 mol / L repair liquid B directly and evenly mixed in a volume ratio of 1:1 have a significant synergistic effect, which can synergistically greatly improve the repair effect of the repaired cracks.

[0082] Although the embodiments of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments.

Claims

1. A microbial composite material for improving the repair effect of concrete cracks, characterized in that: The composite material comprises repair liquid A, repair liquid B and auxiliary materials; Wherein, the volume ratio of the repair liquid A to the repair liquid B is 1:1; The repair solution A is one of the following: a fermentation solution of Sporosarcina pasteurianum, a fermentation supernatant, a bacterial solution, a crude urease extract containing broken bacterial cells, and a crude urease extract; The repair solution B is a mixed aqueous solution of urea and calcium acetate, the molar ratio of the two is 1:1, the solvent is water, and the concentration of calcium acetate is 0.5-2 mol / L; The auxiliary materials include volcanic stone, ceramsite and alumina.

2. The microbial composite material according to claim 1, characterized in that: The repair liquid A is a fermentation liquid of Bacillus pasteurianus; the concentration of calcium acetate in the repair liquid B is 1.5 mol / L; the particle sizes of the auxiliary materials include 0.1-0.2 mm, 0.2-0.4 mm, 0.4-0.6 mm, 0.6-0.8 mm and 0.8-1.5 mm.

3. The microbial composite material according to claim 2, characterized in that: The auxiliary material is ceramsite, and the particle size of the ceramsite is 0.4-0.6mm.

4. The microbial composite material according to any one of claims 1 to 3, characterized in that: The culture medium components and contents used in the preparation of the pasteurian spore octahedralis fermentation broth are as follows: 25-30 g / L yeast extract, 8-12 g / L ammonium sulfate, 5-8 g / L peptone, 0.1-0.2 mol / L urea, 0.13 mol / L Tris, the solvent is water, and the pH value is adjusted to 8.5-9.5 with 2 mol / L HCl; the activation culture conditions of the pasteurian spore octahedralis are 28-35° C., 180-220 r / min, and the culture is carried out on a shaking table for 15-18 hours; after activation, the culture is expanded under the conditions of 28-35° C., 180-220 r / min, and the culture is carried out on a shaking table for 24-30 hours.

5. Use of the microbial composite material according to any one of claims 1 to 4 in repairing concrete cracks.

6. A method for improving the repair effect of concrete cracks using the microbial composite material according to any one of claims 1 to 4, characterized in that: The method adopts a repair process of injecting a repair liquid A and a repair liquid B at low temperature and filling auxiliary materials step by step to repair cracks, so as to improve the crack repair effect.

7. The method according to claim 6, characterized in that: The method comprises the following steps: filling auxiliary materials step by step, i.e. filling the crack with auxiliary materials ≤1.5cm high, ensuring that the materials are evenly accumulated in the cracks, directly mixing the repair liquid A stored in a 4°C refrigerator with the repair liquid B at a volume ratio of 1:1, and using a medical syringe to absorb the mixed solution and slowly inject it into the crack along the crack mouth. This is a repair test, and the repairs are carried out twice a day with a time interval of 6h between each repair. After the materials are cemented, fill with auxiliary materials ≤1.5cm high, and repeat the above steps until the cracks are completely repaired.

8. The method according to claim 6, characterized in that: The initial temperature when injecting the repair fluid is ≤5℃.